Handbook of the libraries, the University of Kansas. - University of Kansas. (University of Kansas Libraries, 1982)
Descriptors: library handbooks, university libraries.
Includes index.
Kansas State Documents Classification Number: E50.1308 : H236
Descriptors: library handbooks, university libraries.
Keywords: Academic libraries / Kansas / Handbooks, manuals, etc.